2001
DOI: 10.1111/j.1525-1497.2001.00537.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving depression outcomes in community primary care practice

Abstract: OBJECTIVE: To determine whether redefining primary care team roles would improve outcomes for patients beginning a new treatment episode for major depression. DESIGN:Following stratification, 6 of 12 practices were randomly assigned to the intervention condition. Intervention effectiveness was evaluated by patient reports of 6-month change in 100-point depression symptom and functional status scales. SETTING:Twelve community primary care practices across the country employing no onsite mental health profession… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(76 citation statements)
references
References 33 publications
2
74
0
Order By: Relevance
“…Using a rating scale from 1 to 5, with 1 indicating “strongly agree” and 5 indicating “strongly disagree,” subjects were asked whether they would be concerned about side effects if they took antidepressant medications (24), and to rate the extent to which they felt antidepressant medications were effective in treating depression. Using a scale from 1 to 4, with 1 indicating “definitely acceptable” and 4 indicating “definitely not acceptable,” subjects were asked to rate the extent to which they viewed taking antidepressants as acceptable for treating depression (19,20). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a rating scale from 1 to 5, with 1 indicating “strongly agree” and 5 indicating “strongly disagree,” subjects were asked whether they would be concerned about side effects if they took antidepressant medications (24), and to rate the extent to which they felt antidepressant medications were effective in treating depression. Using a scale from 1 to 4, with 1 indicating “definitely acceptable” and 4 indicating “definitely not acceptable,” subjects were asked to rate the extent to which they viewed taking antidepressants as acceptable for treating depression (19,20). …”
Section: Methodsmentioning
confidence: 99%
“…Trials of collaborative care have demonstrated increased initiation of and adherence to antidepressant therapy (1921). However, to the best of our knowledge, no studies have examined the impact of collaborative care models on the side effects reported by patients.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23] According to the task force, these trials "screened all patients for depression, enrolled only those screening positive, and returned results of screening to clinicians in the intervention group only." 10 The USPSTF told The BMJ that, if anything, this would have led to more conservative estimates of screening benefit.…”
Section: Featurementioning
confidence: 99%
“…24 Critics point out, however, that none of the four studies included an unscreened control group, and three of the studies compared optimized with usual care, meaning that any benefit in health outcomes could be because of optimized care and not screening (though not all found a benefit). [20][21][22][23] The fourth study provided usual care to both arms but found that the intervention arm, in which providers were told of screening results, "did not lead to improved patient outcomes." 22 Wanda Filer, president of the American Academy of Family Physicians, told The BMJ that the academy supported the task force recommendations on depression screening.…”
Section: Featurementioning
confidence: 99%
“…As mentioned, we found some differences in reported emphases from recommended guidelines, e.g., WHO guideline for the management of depression. 10 This could stimulate and guide educational programs 10,15,[18][19][20][21][22] and possibly also help to develop guidelines that have a better fit with clinical reality. There are several limitations to this study.…”
Section: Discussionmentioning
confidence: 99%